2021
DOI: 10.1007/s15010-021-01645-2
|View full text |Cite|
|
Sign up to set email alerts
|

Key summary of German national treatment guidance for hospitalized COVID-19 patients

Abstract: Purpose This executive summary of a national living guideline aims to provide rapid evidence based recommendations on the role of drug interventions in the treatment of hospitalized patients with COVID-19. Methods The guideline makes use of a systematic assessment and decision process using an evidence to decision framework (GRADE) as recommended standard WHO (2021). Recommendations are consented by an interdisciplinary panel. Evidence analysis and interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 63 publications
0
16
0
2
Order By: Relevance
“…Vitamin D3 supplementation has been hypothesised to affect clinical outcomes in patients with COVID-19, however; this was not successfully confirmed [ 61 , 67 ]. Currently, vitamin D3 supplementation is not recommended [ 68 ]. However, all studies agree that the lack of randomised controlled studies, small cohorts, different dosages and vitamin D formulations, non-standardised study conditions and large heterogeneity between the studies hinders the evaluation and conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D3 supplementation has been hypothesised to affect clinical outcomes in patients with COVID-19, however; this was not successfully confirmed [ 61 , 67 ]. Currently, vitamin D3 supplementation is not recommended [ 68 ]. However, all studies agree that the lack of randomised controlled studies, small cohorts, different dosages and vitamin D formulations, non-standardised study conditions and large heterogeneity between the studies hinders the evaluation and conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the new broad-spectrum antiviral remdesivir, a ribonucleotide analogue that inhibits viral RNA polymerase, has received considerable attention and has been the subject of controversial recommendations: Based on the results of the NIAID-ACTT-1 trial [4], the European Medicines Agency (EMA) concluded that the benefits of remdesivir in COVID-19 patients with pneumonia who require supplemental oxygen (low-or high-flow oxygen therapy or other noninvasive ventilation) outweigh the risks, and that the drug could be approved in the European Union under special conditions; by contrast, the WHO, in its guideline [5] based on the SOLIDARITY trial [6], advises against the use of remdesivir in hospitalized patients with COVID-19. The European Respiratory Society (ERS) and the Association of the Scientific Medical Societies in Germany (AWMF) did not advocate for or against remdesivir therapy in their treatment guidelines because of continuing uncertainties about its potential benefits [7][8][9]. The results of the RECOVERY trial [10] led WHO and EMA to recommend low-dose dexamethasone in COVID-19 patients [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, IL-10 plays a beneficial role against coronavirus infection. Current clinical guidelines for treating COVID-19 with ARDS is triple therapy: remdesivir, tocilizumab (anti-IL-6 monoclonal antibody), and corticosteroid [ 147 ]. Remdesivir is the anti-SARS-CoV2 agent.…”
Section: Immune Pathogenesis Of Ards: Role Of Th17 Immunitymentioning
confidence: 99%